Contribuições dos movimentos sociais na democratização do acesso à educação: a luta do MST em São Paulo pelo acesso à educação - Chaves, Rodolfo de Jesus (Universidade Federal de São Carlos, 2011)
Works on the organization, forms of struggle and reproduction of social movements have taken steam in recent years. Among the movements that advocate land reform, there is the MST (Movement of Landless Rural Workers) which has changed the reality of peasant populations who joined the ranks of the Movement to win their rights. That these rights are not limited only to the conquest of land to work, as we observe the movement has diversified its set of demands, so try to secure rights such as labor, health, education, etc.. From this perspective, this study aims to investigate the contributions of the MST in the struggle for access to school education for rural workers. As resources to achieve this goal, we mobilized a large bibliography on the subject, visited rural settlements of the Movement to meet the socio-educational and interviewed by collecting data that were helpful to the writing of this work. While we value the entire history of organization and struggle of rural workers, our study was devoted to the most recent period of history which will re-democratization of Brazil in 1980 until the last years of the 2000s.
Keywords: Educação rural; Educação do campo; Trabalho e educação; Reforma agrária; Movimento Sem Terra; Rural education; Agrarian reform; Landless movement; CIENCIAS HUMANAS::EDUCACAO